Genomic analysis reveals Lactobacillus sanfranciscensis as stable element in traditional sourdoughs - Vogel, Rudi F; Pavlovic, Melanie; Ehrmann, Matthias A; Wiezer, Arnim; Liesegang, Heiko; Offschanka, Stefanie; Voget, Sonja; Angelov, Angel; Böcker, Georg; Liebl, Wolfgang (Microbial cell factories, 2011)
Sourdough has played a significant role in human nutrition and culture for thousands of years and is still of eminent importance for human diet and the bakery industry. Lactobacillus sanfranciscensis is the predominant key bacterium in traditionally fermented sourdoughs. The genome of L. sanfranciscensis TMW 1.1304 isolated from an industrial sourdough fermentation was sequenced with a combined Sanger/454-pyrosequencing approach followed by gap closing by walking on fosmids. The sequencing data revealed a circular chromosomal sequence of 1,298,316 bp and two additional plasmids, pLS1 and pLS2, with sizes of 58,739 bp and 18,715 bp, which are predicted to encode 1,437, 63 and 19 orfs, respectively. The overall GC content of the chromosome is 34.71%. Several specific features appear to contribute to the ability of L. sanfranciscensis to outcompete other bacteria in the fermentation. L. sanfranciscensis contains the smallest genome within the lactobacilli and the highest density of ribosomal RNA operons per Mbp genome among all known genomes of free-living bacteria, which is important for the rapid growth characteristics of the organism. A high frequency of gene inactivation and elimination indicates a process of reductive evolution. The biosynthetic capacity for amino acids scarcely availably in cereals and exopolysaccharides reveal the molecular basis for an autochtonous sourdough organism with potential for further exploitation in functional foods. The presence of two CRISPR/cas loci versus a high number of transposable elements suggests recalcitrance to gene intrusion and high intrinsic genome plasticity.